Identification and drug binding capabilities of tubulin in the nematode Ascaridia galli. - Ireland, C; Clayton, L; Gutteridge, W; Pogson, C; Gull, K (1982)
Cell extracts of Ascaridia galli bind colchicine in a manner suggesting the presence of a tubulin-like protein. Column chromatography of these extracts on DEAE-Sephadex yielded only one peak with colchicine-binding activity. Single peaks of radioactivity in this same position were obtained on chromatography of extracts prelabelled with either [3H]colchicine or [3H]parbendazole. Sodium dodecyl sulphate polyacrylamide gel electrophoresis and two dimensional gel electrophoresis of the fractions making up the peaks indicated the presence of two proteins which co-migrate with mammalian brain alpha- and beta-tubulin markers. More detailed investigation showed that the A. galli tubulin has a slightly different alpha-subunit when compared with mammalian tubulin.